Prenatal exposure to tobacco and cannabis, early cannabis initiation, and daily dual use of combustible cigarettes and cannabis during young adulthood - De Genna, Natacha M. (Addict Behav, 2021)
INTRODUCTION. Daily combustible cigarette use is common among cannabis users, and dual use of cigarettes and cannabis is associated with detrimental outcomes. This study addresses gaps in the literature by examining data from the prenatal and adolescent phases of a prospective, longitudinal study to predict adult daily dual use. METHODS. Young adult offspring (M age = 22.8 years, 53% female) from a prenatal cohort reported on combustible cigarette, and cannabis use (N = 500, 58% Black, 42% White). Pathways to daily dual use were modeled using variables from the gestational and adolescent phases of the study including prenatal tobacco, alcohol, and cannabis exposures; ages at initiation of cigarettes and cannabis; and adolescent learning/memory, impulsivity, and behavior problems. RESULTS. Prenatal cannabis and tobacco use were not directly linked to adult daily dual use of cannabis and tobacco. However, structural equation modeling revealed three significant indirect pathways from prenatal cigarette and cannabis exposures to adult daily dual use of cigarettes and cannabis via early cigarette initiation, early cannabis initiation, and adolescent behavior problems. CONCLUSIONS. This study identified pathways from prenatal cannabis and tobacco exposure to adult daily dual use, in addition to clarifying adolescent outcomes that may be part of the pathways. In a climate of growing acceptance of cannabis use and increasing legalization of recreational use, these findings serve as a warning that early exposure to cannabis may have an important role in shaping long-term dual use of tobacco and cannabis.